2004
DOI: 10.1159/000080314
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Gastroesophageal Reflux Disease in Adults: An Individualized Approach

Abstract: Until the 1990s, most therapeutic trials in gastroesophageal reflux disease (GERD) focussed upon endoscopic lesions. In fact the correlation between patient symptoms and both the presence and grade of esophagitis is very poor. The classical criteria for the assessment of therapeutic efficacy in GERD have therefore been revised, and there is now a consensus that the relief of symptoms and the long-term control of the disease are the primary aims of therapy for the majority of patients. Proton pump inhibitors (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 99 publications
1
16
0
2
Order By: Relevance
“…It is true that PPI is less effective in NERD patients compared with in erosive GERD patients. Like other studies [33,34], our recent study clearly confirmed this observation [24] (Fig. 4).…”
Section: Effect Of Gerd On Quality Of Life (Qol) In Japanese Populatisupporting
confidence: 90%
“…It is true that PPI is less effective in NERD patients compared with in erosive GERD patients. Like other studies [33,34], our recent study clearly confirmed this observation [24] (Fig. 4).…”
Section: Effect Of Gerd On Quality Of Life (Qol) In Japanese Populatisupporting
confidence: 90%
“…Kitchin and Castell (16) concluded that, although there were few well-designed, placebo- controlled trials, lifestyle interventions are effective in treating GERD. In contrast, Galmiche et al (17) reported that, while appropriate for promoting general health, many of lifestyle changes are not of benefit in alleviating GERD symptoms. Salyers et al (18) also reported that only 12% of 502 GERD patients received documented counseling regarding lifestyle modifications.…”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12] However, PPIs are less effective in NERD patients than in erosive esophagitis patients. [13][14][15][16] In addition, hiatal hernia is less common and gastric atrophy is more severe in patients with minimal change esophagitis than in those with erosive esophagitis. 13,17 These findings suggest that the characteristics and pathophysiology of minimal change esophagitis differ from those of erosive esophagitis.…”
Section: Introductionmentioning
confidence: 99%
“…13,17 Moreover, PPIs are less effective in NERD patients than in those with erosive esophagitis patients. [13][14][15][16] These findings suggest that the pathophysiology of minimal change esophagitis may be different from that of erosive esophagitis, and indicate that the development of more effective treatment options is necessary.…”
mentioning
confidence: 99%